1986
DOI: 10.1038/320155a0
|View full text |Cite
|
Sign up to set email alerts
|

Phenol and HCl at 550 °C yield a large variety of chlorinated toxic compounds

Abstract: During the past decade it has been shown conclusively that the incineration of municipal and industrial wastes gives rise to emissions of chlorinated dibenzodioxins and dibenzofurans. However, the mechanism by which these toxic compounds are formed has not yet been fully established. Some researchers believe that the presence of organically bound chlorine is necessary, but others consider that inorganic forms of chlorine may also participate in the process. We now report the synthesis of a large number of chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…However, some incinerator observations favor formation in the colder region of the post combustion zone. Such evidence is reviewed, by way of example, briefly below for the post combustion regions of three incinerators: PEI (23), Pittsfield (24), and Oswego (25) (Tables 2, 3,4). Although these are three (Tables 2 and 3); PCDD's increase while PCDF's remain unchanged (Table 4).…”
Section: Relationship Of Laboratory Findings To Observations From Incmentioning
confidence: 94%
See 2 more Smart Citations
“…However, some incinerator observations favor formation in the colder region of the post combustion zone. Such evidence is reviewed, by way of example, briefly below for the post combustion regions of three incinerators: PEI (23), Pittsfield (24), and Oswego (25) (Tables 2, 3,4). Although these are three (Tables 2 and 3); PCDD's increase while PCDF's remain unchanged (Table 4).…”
Section: Relationship Of Laboratory Findings To Observations From Incmentioning
confidence: 94%
“…Recent studies by Eklund, et al. (4)(5)(6) lead to the conclusion that the heating in air of almost any combination of C, H, and Cl-compounds (organic and inorganic gaseous reactants) can lead to PCDD/F's under certain conditions. The question of rates is not addressed by these schemes.…”
Section: Formationmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been confirmed that toxic chlorinated organic compounds such as polychlorinated dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs) are formed during combustion of compounds containing chlorine substituents (1)(2)(3)(4)(5)(6)(7)(8). Particularly, pyrolysis of polychlorinated biphenyls (PCBs) has been investigated in detail regarding PCDFs (9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…An undesirable characteristic of incinerators is that they tend to produce and/or emit toxic compounds, such as heavy metals and polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs). [1][2][3][4][5] Other thermal technologies are available to explore the treatment of hazardous and nonhazardous waste, like gasification. 6 Thermal destruction of a carbonaceous material can occur under three main conditions based on the availability of oxygen: (1) combustion (oxidizing atmosphere), (2) gasification (limited oxygen producing a reductive atmosphere), and (3) pyrolysis (absence of oxygen).…”
Section: Introductionmentioning
confidence: 99%